Answer:
f(2) =5
Step-by-step explanation:
We have a function f(x) = 3x-1
When we find f(2) ,let x=2
f(2) = 3*2-1
= 6-1
=5
Answer:
Step-by-step explanation:
hello :
h(x) = x² – 5x + 7
h(-2) = (-2)² – 5(-2) + 7 =4+10+7 =21
h(-5) = (-5)² – 5(-5) + 7= 25+25+7 =57
h(-8) = (-8)² – 5(-8) + 7 = 64+40+7=111
75d+8w+25
Part A)
75 and 8 are coefficients because coefficients are the numbers before and multiplied to the variable.
d and w are variables because variables aresymbols to represent the unknown numbers.
25 is the constant because constants are not affected by the variable.
Part B)
75d+8w+25
75(5)+8(48)+25 replace the variables
375+384+25 multiply
784 add
Part C)
No, because his stipend is a constant, and constants are not affected by the variable.
Answer:
sure
Step-by-step explanation: